2019
DOI: 10.1038/s41598-019-55106-w
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis drug FTY-720 toxicity is mediated by the heterotypic fusion of organelles in neuroendocrine cells

Abstract: FTY-720 (Fingolimod) was one of the first compounds authorized for the treatment of multiple sclerosis. Among its other activities, this sphingosine analogue enhances exocytosis in neuroendocrine chromaffin cells, altering the quantal release of catecholamines. Surprisingly, the size of chromaffin granules is reduced within few minutes of treatment, a process that is paralleled by the homotypic fusion of granules and their heterotypic fusion with mitochondria, as witnessed by dynamic confocal and TIRF microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Altered levels of mitochondrial proteins were reported in retinal neurons in models of diabetic retinopathy [ 61 ] and glaucoma [ 62 ]. Results from our study are consistent with studies on neuroprotective properties of FTY in other models where FTY improved mitochondrial stability and restored mitochondrial dynamics under oxidative stress conditions [ 20 , 63 , 64 , 65 ]. Our present study did not investigate the changes in mitochondrial function.…”
Section: Discussionsupporting
confidence: 91%
“…Altered levels of mitochondrial proteins were reported in retinal neurons in models of diabetic retinopathy [ 61 ] and glaucoma [ 62 ]. Results from our study are consistent with studies on neuroprotective properties of FTY in other models where FTY improved mitochondrial stability and restored mitochondrial dynamics under oxidative stress conditions [ 20 , 63 , 64 , 65 ]. Our present study did not investigate the changes in mitochondrial function.…”
Section: Discussionsupporting
confidence: 91%
“…These merging organelles then increased in size and roundness at 15 min of initiation of the FTY-720 incubation. The changes were confirmed by electron microscopy that additionally showed a dramatic change in the fusion properties of chromaffin granules in the interior of the cellular cytoplasm [64] as seen in Figure 2. The sequence of events indicated that during FTY-720 treatment (Figure 2): (i) chromaffin granules in the cytosol initiate processes of homotypic fusion between themselves, and fissions to form microvesicles, (ii) with a small delay of minutes chromaffin vesicles started to fuse even with mitochondria increasing the size and roundness of these organelles, (iii) these heterotypic fusions ended in the formation of giant mitochondrial round structures containing multiple vesicular dense cores in their interior.…”
Section: Fty-720 Induces the Heterotypic Fusion Of Organellesmentioning
confidence: 61%
“…Our more recent study revealed that FTY-720 not only mimics sphingosine properties in relation to the fusion of vesicles and the plasma membrane during exocytosis but also exhibits new properties in relation to the fusion and fission of other cellular structures such as mitochondria that had not been reported previously [64].…”
Section: Fty-720 Induces the Heterotypic Fusion Of Organellesmentioning
confidence: 64%
See 2 more Smart Citations